Forewarning incidence of American boll worm (Heliothis armigera H.) of cotton at Akola in Vidarbha region of Maharashtra - GHOSH, KGHOSH; RAJAVEL, MRAJAVEL; SAMUI, R.P.; SINGH, G.P.; KARMAKAR , C. (MAUSAM, 2014)
A study on pest population of American boll worm (Heliothis armigera H.) in cotton crop as influenced by weather parameters like rainfall (RF), maximum temperature (Tmax), minimum temperature (Tmin), morning relative humidity (RH I), evening relative humidity (RH II) and bright sunshine hours (BSS) and its statistical correlation was undertaken with data recorded at Dr. Punjabrao Deshmukh Krishi Vidhyapeeth, Akola. The maximum activity and damage due to high population of Heliothis was observed during 35th to 50th standard weeks. Maximum temperature (40th week) and minimum temperature (37th week), morning and evening relative humidity during 38th week play an important role in pest infestation during 40th standard week. Flowering to boll formation stages of the crop suffered heavy incidence of Heliothis. Critical weather parameters causing the outbreak of Heliothis in Akola was maximum temperature around 32 °C and minimum temperature around 23 °C, morning relative humidity below 88%, evening relative humidity below 60% and hours of bright sunshine above 6.5 hrs / day.